Socio Demographic and Travel Related Variables Affecting Tourist Route Choice Behaviors. Case of Study Samarqand city, Uzbekistan. - Nodira Begim Mukhamadalieva; Gulsum Tilyabaeva (Indonesian Journal of Law and Economics Review, 2020)
The development of routes in tourism has gained prominence in recent years. One key aim of these routes, apart from attracting tourists to an area, is to tie-up several attractions that would independently not have the potential to entice visitors to spend time and money. Using a cooperation effect promises to have greater pulling power, and it also disperses visitors’ money among a larger number of recipients. Many cities promoting a different type of routes that, in some way, domesticate the gaze of tourists. The most famous routes across the world are the catalog of city resources and offer some of them, which are “consumed” in a homogenous way. The main question of this thesis is (1) how to identify routes in a designated area (2) which socio-demographic and travel related variables are influencing tourists route choice behavior. The questionnaire-based survey was conducted in Samarqand city among local tourists.